Detection of endocrine disrupting chemicals and evidence of their effects on the HPG axis of the European anchovy Engraulis encrasicolus. (June 2017) - Miccoli, Andrea; Maradonna, Francesca; De Felice, Andrea; Caputo Barucchi, Vincenzo; Estonba, Andone; Genangeli, Michele; Vittori, Sauro; Leonori, Iole; Carnevali, Oliana
Abstract: Natural/synthetic Endocrine Disrupting Chemicals (EDCs) may display estrogenic activity and a lower potency than 17β-estradiol. Nonetheless, their concentrations and additive effects can affect the endocrine system and reproductive processes related to the Hypothalamic–Pituitary–Gonadal (HPG) axis. Because of their persistence in both the environment and biological systems, they ultimately target multi-level predators, including humans. We detected presence and effects of xenobiotics on wild anchovy Engraulis encrasicolus in the Western Adriatic Sea. Twenty-one PCBs and five organochlorines were detected on the order of ng g −1 ; vitellogenin, vitellogenin receptor and genes encoding for the zona radiata proteins were evaluated in gonad and/or liver and found transcribed in male specimens; in addition, intersex was histologically identified in the 13% of testis. Our results have developed the understanding of the European anchovy's reproductive toxicological risk and our approach could assist the comprehension of the complex dynamics of commercially relevant Teleost species. Highlights: PCBs and organochlorines detected in wild European anchovy along Western Adriatic. Characterization and gene expression of vitellogenin and its receptor in anchovy. Wild male anchovy specimens transcribe female-specific reproduction-related mRNAs. Intersex condition found in male gonads.